Ultrasound Biomicroscopy Detects Peters’ Anomaly and Rieger’s Anomaly in Infants - Wen-Si Chen; Dao-Man Xiang; Lan-Xiang Hu (Journal of Ophthalmology)
Aim. Congenital corneal opacities (CCOs) are the major causes of early visual deprivation in infants. Balloon ultrasound biomicroscopy (UBM) examination is an effective method to diagnose CCO. However, whether it is suitable for children examination is still unknown. Methods. 26 Peters’ anomaly (PA) or Rieger’s anomaly (RA) infants with congenital corneal opacities (CCO) (40 eyes) underwent UBM examinations to study their imaging features. Results. Based on the results, they were divided into UBM Dx-Type I: Descemet’s membrane (DM) and endothelium have heterogenous or discontinuous echo accompanied with corneal stroma echo-enhanced or shallow anterior chamber. Type II: Type I alteration plus abnormal strand of iris extended to the border of the posterior corneal defect or iridocorneal adhesion. Type III: Type I or II combined with the abnormal hyperechoic lens, lens luxation, or keratolenticular adhesion. Type IV: echoes of the DM and the endothelium are continuous, corneal stroma echo is enhanced, and an abnormal strand of peripheral iris extends to the prominent Schwalbe line, accompanied by iris stroma or pupil heteromorphism and a shallow or flat anterior chamber. Conclusion. UBM not only could accurately evaluate the anterior segment abnormalities in CCO infants but also would be a step forward for the management of PA- and RA-associated CCO.